Arab world's growing contribution to global leishmaniasis research (1998-2017): a bibliometric study - Samah W. Al-Jabi (BMC, 2019)
Abstract Background Leishmaniasis is a parasitic disease caused by a protozoan of the Leishmania genus, and is considered a neglected tropical disease. It still remains a main public health concern at global level and in Arab world mainly in low-income countries. Therefore, this study was designed to evaluate the Arab world's growing contribution to global leishmaniasis research. Methods This study describes a bibliometric review of all leishmaniasis research publications published between January 1998 and December 2017 indexed on the Scopus database. Results The total number of publications published at global level was 17,570 papers, which achieves an average annual productivity of 878.50 papers publications. Brazil was responsible for the greatest output with the total number of publications of 3865 followed by the Unites States (n = 2729), India (n = 2119), the United Kingdom (n = 1363), and Spain (n = 1274). By limiting the analysis to the publications that have been published by Arab world, the research productivity was 993 papers, which represents 5.65% of total research output at global level in research regarding leishmaniasis. Tunisia was responsible for the greatest output from Arab world with the total number of publications of 297 followed by Sudan (n = 192), Saudi Arabia (n = 131), Morocco (n = 119) and Egypt (n = 67). Since 1998, the growth of publications on leishmaniasis fluctuates, overall showing a rising trend in both global and Arab world. There is a highly significant correlation between publication productivity related to leishmaniasis at global level and the Arab world (r = 0.936; p-value< 0.001). Leishmaniasis treatment, intracellular mechanism of infection, and lifecycle of leishmania are the major current hot topics for the research in this subject at global level and the Arab world. Conclusions The current study presents a novel review of the current Arab leishmaniasis-related research, and how these results are related to worldwide output. In comparison to the global research output, the Arab world produced less leishmaniasis research. The data presented in the current study by this innovative approach may serve relevant researchers to direct the global leishmaniasis research to Arab counties in which leishmaniasis is endemic.